Cost Comparison of Operatively Treated Ankle Fractures Managed in an Inpatient versus Outpatient Setting - Clayton C. Bettin MD; Mikayla Lyman BS; Alexej Barg MD; Charles L. Saltzman MD; David Rothberg MD; Richard Nelson (Foot & Ankle Orthopaedics, 2016)
Category: Trauma Introduction/Purpose: Although choices physicians make profoundly impact the cost of healthcare, few surgeons know actual costs. Without valid cost information, surgeons cannot understand how their choices impact the total cost of care. We leveraged a validated value analytics framework to efficiently allocate clinical care costs to individual patient encounters in an effort to understand the sources and variation of cost of care for a putatively straightforward and common orthopaedic problem. Methods: We conducted a retrospective cost analysis on all isolated, operatively treated ankle fractures from a Level 1 trauma hospital and affiliated outpatient surgery center between 2013 and 2015. Patients were categorized based on whether they were treated on an inpatient or outpatient basis, and records were reviewed to determine the presence of confounding variables as well as readmission and emergency department (ED) visits within 90 days after surgery. Actual costs were determined using a validated episode of care costing system and analyzed using multivariate regression analysis. Results: 148 patients (61 inpatients, 87 outpatients) with isolated, operatively treated ankle fractures were included. After controlling for confounding variables, outpatient care was associated with 31.6% (95% CI: 19.8% - 41.8%) lower costs compared to inpatient care. Obese patients had 21.6% (95% CI: 5.8% - 39.8%) higher costs compared to patients who were not obese. There was no difference in reoperation, readmission or return visits to the ED for patients treated on an inpatient or outpatient basis. Conclusion: Inpatient surgical care is clearly more expensive than outpatient care primarily due to higher facility and labor costs without a clear advantage relative to lower readmission or ER visit rates. Where medically appropriate, this analysis suggests ankle fracture surgery should be provided in an outpatient surgical facility to provide the greatest value to the patient and society.